HUBUNGAN ANTARA JENIS KONTRASEPSI SUNTIK DAN LAMA PEMAKAIAN DENGAN KENAIKAN BERAT BADAN PADA AKSEPTOR KB - Betty Iriyanti Br Panjaitan; Yusrohadi M.; Yuliawati Yuliawati (Jurnal Kesehatan Metro Sai Wawai, 2017)
Indonesia has fast population growth approximately 255 million people in 2015, Lampung Province 8.11 million people. To solve the problems in Indonesia, the government implemented a family planning program. The type of injecting contraceptive 46.67%, Lampung 34.4%, Metro City 26.5%, in the Amrina Midwife Private Practice 48.97%. This type of hormonal contraception is increasingly used, the side effects is weight increasing. The results of prasurvey on 10 injection contraceptive in Amrina Midwife Private Practice 6 (60%) sample experience weight increasing for 2,5 years. The purpose of the study is to know the correlation of contraceptive type and the duration using with acceptor weight increases. The study method is quantitative analytic with cross sectional approach. The population of injecting contraceptive acceptor was 120 acceptors, using Simple Random Sampling counted in 92 respondents. The research period is in Maret until May, instrument data collection through documentation, univariate and bivariate analysis using chi square statistical test. The result of research proportion of weight in injected acceptor was 68,5%. The proportion of contraceptive type injection was 60,9% and the proportion of time usage was 64,1%. The relation between type of family injection with weight injection acceptor is p= 0,032 or p ≤ 0, 05, the correlation between the duration of injectable contraceptive use and the increase in body weight of the injection acceptor is p= 0,000 or p ≤ 0.05. The conclusion shows that there is a significant correlation between contraception type and duration of usage with weight increasing in contraceptive acceptor.